Achievement Levels of Middle School Students in the Standardized Science and Technology Exam and Formative Assessment Probes: A Comparative Study - Nermin Bulunuz; Omer Faruk Tavsanli; Mizrap Bulunuz; Funda Karagoz (Journal of Education in Science, Environment and Health)
The present study has two aims. Firstly, it aims to determine eighth grade students’ conceptual understanding of floating and sinking through formative assessment probes. Secondly, it aims to determine whether or not there is a significant difference between students’ performance in formative assessment probes and their achievement in the Standardized Science and Technology Exam (TEOG 1) exam.  The sample of this research is 61 eighth grade students from a central middle school in Eskişehir. Data collection tools are four two-stage formative assessment probes and the scores of the student taken from the first TEOG 1 exam. The answers of the students to the two-stage probes were scored by use of a rubric. Findings indicated that most of the students either: a) both chose incorrect answer and did not write correct scientific explanation (%41);  b) chose correct answer but did not write correct scientific explanation (%33); and c) chose correct answer but wrote partially correct explanation (%43). This result indicates the poorness of students' explanation and interpretation skills in formative assessment probes. In addition, the findings of the dependent sample t-test results also indicate that there is a significant difference between the scores of the students taken from the standardized science test (TEOG 1) and the formative assessment probes on the concepts of floating and sinking.  This finding shows that the students are more successful on standardized science test than the formative assessment probes in general. These research findings, suggest that students should be exposed to teaching practices based on "formative assessment" that promotes the development of students’ skills of explaining, interpreting, and reasoning rather than multiple-choice tests in science lessons.